HTLV seroprevalence in pregnant women: integrative review (Research, Society and Development, 2021)
Introduction: Speculated that about 10 to 20 million individuals are contaminated by HTLV in the world. Brazil reaches the top positions in the ranking. The means of spreading the virus occur through breastfeeding, vertical, sexual and parenteral transmission. The marker to identify the high risk of TMI is the PVL of HLTV-1 in mononuclear cells in the peripheral blood of the pregnant woman. Objective: to investigate the seroprevalence of HTLV in pregnant women, performing an integrative review of the subject in question and to analyze the preventive forms for the offspring of the host. Methodology: Refers to an integrative review using online databases such as: Google School, BIREME, SCIELO, PUBMED, FIOCRUZ, MS, USP, LILACS, Science Direct. Results and Discussions: The complexity of diagnosing mild cases located in plasma and the scarcity of confirmatory tests for the detection of anti-HTLV by PCR, ELISA or Western Blot, complicate the diagnosis of ATLL in adults aged 20 to 30 years, which occurs after the infection in children. Breastfeeding becomes the main route of transmission, surpassing the cases reported by sexual and parenteral routes. However, since research on transmission, whether by sexual route or TMI, is not employed in Brazil, it causes recurrent endemicity in the country. Making the prevention of the incidence the most appropriate means of combating it, since there are no vaccines or treatment. Conclusion: The SUS needs to improve epidemiological research to investigate endemicity and provide tracking and assistance for HIV-positive pregnant women.